(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The biosorption characteristics of mercury ions from aqueous solution using jute nanofibers, a cellulose- based natural fiber, were explored as a function of pH, nanofiber concentration, contact time and temperature. Jute nanofibers were obtained after wet milling the jute fibers and subsequently their morphology was assessed by various spectroscopy and microscopy techniques. The maximum biosorption capacity of the fiber calculated by the Langmuir model was found to be 85.5 mg g^1. The adsorption experiments revealed that ion-exchange and complexation mechanisms were principal role in the biosorption process. The present experimental evidence implies that jute nanofibers could be a potential natural biomaterial for the removal of environmental contaminations from textile and chemical industries.